Ivabradine Improves Left Ventricular Function During Chronic Hypertension in Conscious Pigs. Issue 1 (January 2015) - Rienzo, Mario; Melka, Jonathan; Bizé, Alain; Sambin, Lucien; Jozwiak, Mathieu; Su, Jin Bo; Hittinger, Luc; Berdeaux, Alain; Ghaleh, Bijan
<x xml:space="preserve">Abstract</x> During chronic hypertension, increases in heart rate (HR) or adrenergic stimulation are associated with maladaptive left ventricular responses as isovolumic contraction and relaxation durations failed to reduce, impeding filling. We, therefore, investigated the effects of acute selective HR reduction with ivabradine on left ventricular dysfunction during chronic hypertension. Accordingly, chronically instrumented pigs received angiotensin II infusion during 4 weeks to induce chronic hypertension. Left ventricular function was investigated while angiotensin II infusion was stopped. A single intravenous dose of ivabradine was administered at days 0 and 28. Dobutamine infusion was also performed. HR was increased at day 28 versus day 0. Paradoxically, both isovolumic contraction and relaxation times failed to reduce and remained unchanged (57±3 versus 58±3 ms and 74±3 versus 70±3 at day 28 versus day 0, respectively). At day 28, ivabradine significantly reduced HR by 27%. Concomitantly, abnormal ventricular responses were corrected because both isovolumic contraction and relaxation times were significantly reduced while filling time was improved. Similarly at day 28, maladaptive responses of isovolumic contraction and relaxation to dobutamine were no longer observed during HR reduction with ivabradine. Correction of HR reduction with pacing showed that non-HR–related mechanisms also participated to these beneficial effects. In this model of chronic hypertension and left ventricular hypertrophy, acute HR reduction with ivabradine corrects the maladaptive responses of cardiac cycle phases by restoring a normal profile for isovolumic contraction and relaxation both at rest and under adrenergic stimuli, ultimately favoring filling.